Strategic management - Rothaermel, Frank T. (New York, NY : McGraw Hill LLC, 2024)
"The market for strategy texts can be broadly separated into two overarching categories: traditional application-based and research-based. Traditional application-based strategy books represent the first-generation texts with first editions published in the 1980s. The researchbased strategy books represent the second-generation texts with first editions published in the 1990s. I wrote this text to address a needed new category-a third generation of strategy content that combines into one the student-accessible, application-oriented frameworks of the first-generation texts with the research-based frameworks of the second-generation texts. The market response to this unique approach to teaching and studying strategy continues to be overwhelmingly enthusiastic"--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Strategic planning; Management